ESTRESSORES NO PERÍODO GESTACIONAL E ATRASO NO DESENVOLVIMENTO NEUROPSICOMOTOR NO SEGUNDO ANO DE VIDA, COORTE BRISA, SÃO LUÍS-MA - LIMA, Nathália Isabella Pavão Pinto (2019)
A set of stressors may act during pregnancy resulting in delayed neuropsychomotor development, however, the relationships between these stressors need to be further explored. Objective: This study investigated the direct and indirect pathways of the association between gestational stressors and neuropsychomotor developmental delay in the second year of life. Methods: This is a prospective study involving data from the BRISA Prenatal Cohort, São Luís, in three moments: 25th week of intrauterine life (baseline), birth (1st follow-up) and second year of life of the child (2nd follow-up). A theoretical model was built to analyze direct and indirect pathways from the Socioeconomic Situation (SES) and the gestational period stressors (pregestational BMI, mother's age, diabetes, hypertension, cesarean section, gestational age) reaching the outcome Neuropsychomotor Development Delay in the second year of the child, a multidimensional construct forming shared variance between the Bayley III scale components (cognition, expressive language, receptive language, fine motor and gross motor). Results: The best SES had a total protective effect on Neuropsychomotor Development Delay (CP = -0.202, p = 0.001), but also had an indirect risk effect of the outcome (CP = 0.098, p = 0.017), passing through the pathway reduction in gestational age. The highest pregestational BMI had a direct protective effect (CP = - 0.187, p = 0.032) and also an indirect risk effect for the outcome (CP = 0.134, p = 0.034), by a sum of the pathways that passed through gestational diabetes or hypertension-reduction of gestational age. Gestational diabetes had a total risk effect for Neuropsychomotor Developmental Delay (CP = 0.280, p = 0.50). More proximally, the higher gestational age had a protective effect on the outcome (CP = -0.203, p <0.001). Conclusion: Gestational stressors acted in a dependent manner resulting in Neuropsychomotor Developmental Delay in the second year of life. The worst economic situation contributed more distally to the risk; while maternal malnutrition along with other metabolic changes in pregnancy: obesity, hypertension and diabetes were also triggers for the outcome. Proximally, younger gestational age was a risk for Neuropsychomotor Developmental Delay.